Proposing an Efficient and Democratic Policy of General Election Budget for Promoting Local Fiscal Autonomy - Koeswara, Hendri; Liesmana, Roza; Hanida, Rozidateno P.; Muluk, Saeful (UI Scholars Hub, 2014)
This research aims to generate general picture of Direct Election for Regional Leader’s (Pemilukada) funding, identify the main problem concerning Pemilukada budget, and suggest practical recommendation on managing Pemilukada budget. This is a qualitative research, using the data collection techniques of in-depth interview and Focus Group Discussion, as well as document analysis on Pemilukada budget and Regional Budget (APBD). The location of the research is in Solok and Bandung District. Both are chosen based on their characteristic of Pemilukada budget best practice and their regional fiscal capacity. The result of this research is a model for Pemilukada budget as instructed by the Law that at present has not been effective in minimizing various problems concerning the implementation of general election at regional level. Pemilukada is budgeted in APBD, heavily encumbering regional finance; therefore regional government’s work plan should be rationalized on the fiscal year of Pemilukada. Recommendation for a model for funding Pemilukada is to budget Pemilukada through National Budget (APBN).